2021
DOI: 10.1093/rheumatology/keab372
|View full text |Cite
|
Sign up to set email alerts
|

The sFlt-1 to PlGF ratio in pregnant women with rheumatoid arthritis: impact of disease activity and sulfasalazine use

Abstract: Objectives An elevated sFlt-1/PlGF-ratio has been validated as a significant predictor of preeclampsia, but has not been established in women with rheumatoid arthritis (RA). We explored whether the sFlt-1/PlGF-ratio could be altered due to disease activity in RA, and could be applied in this population to predict preeclampsia. Since sulfasalazine has been suggested to improve the angiogenic imbalance in preeclampsia, we also aimed to examine whether sulfasalazine could affect sFlt-1 or PlGF l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Our study has implications for the treatment of PE with or without FGR. Until now, research has focused on ways of reducing sFlt-1, by using drugs that have been shown to lower placental sFlt-1 release in vitro 22,23 , suppressing placental sFlt-1 production with short-interfering RNA 24 or removing excess sFlt-1 through apheresis [25][26][27][28] . The concept behind these approaches is that reducing sFlt-1 will normalize the level of free circulating PlGF.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has implications for the treatment of PE with or without FGR. Until now, research has focused on ways of reducing sFlt-1, by using drugs that have been shown to lower placental sFlt-1 release in vitro 22,23 , suppressing placental sFlt-1 production with short-interfering RNA 24 or removing excess sFlt-1 through apheresis [25][26][27][28] . The concept behind these approaches is that reducing sFlt-1 will normalize the level of free circulating PlGF.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, this pattern has also been witnessed with other drugs such as pravastatin or sulfasalazine, which have shown significant sFlt-1-lowering properties in both placental tissues and animal models, although these actions were not apparent when examined in human patients. [16][17][18][19][20] One possibility is that the doses applied in experimental models were much higher compared to the concentrations administered in clinical studies. Indeed, when the C max equivalent of 40 mg esomeprazole (5 µmol/L) was applied in primary tissues, it did not induce a significant reduction in sFlt-1, in contrast with concentrations of 50 or 100 µmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…PlGF and sFlt-1 levels are elevated in both the serum and synovial fluid in RA, and their levels in synovial fluid correlate with disease activity [ 84 ]. According to a study by Neuman et al, the sFlt1/PlGF ratio is not influenced by disease activity in pregnant women with RA, and a cut-off ≤38 can be used to rule out pre-eclampsia [ 87 ].…”
Section: Sflt1/plgf Ratio and Rheumatoid Arthritismentioning
confidence: 99%